Variants of inward disorder pattern and self-awareness features among elementary school children with different dysontogenesis forms - Tatiana Adeeva; Inna Tikhonova; Svetlana Khazova (Social Welfare: Interdisciplinary Approach)
This study explored variants of inward disorder pattern (IDP) among elementary school children with different dysontogenesis forms. IDP is considered a complex integrative construct that affects I-concept development and is significant for an individual’s successful social adaptation. The sample consisted of 84 participants – elementary school children with visual, hearing, speech impairments, and mental development disorder. Their average age is 9. The interview was conducted individually.